2019
DOI: 10.1021/acs.jced.9b00352
|View full text |Cite
|
Sign up to set email alerts
|

Novel Isopropoxy Group-Functionalized UiO-66 with a High Hydrogen Chloride Adsorption Capacity

Abstract: In this paper, a novel isopropoxy group-functionalized UiO-66 (UiO-66-IPO) was synthesized by a general strategy and then used as an adsorbent for the removal of hydrogen chloride from aqueous solutions. The as-synthesized product was characterized by X-ray powder diffraction, scanning electron microscopy, thermal gravimetric analysis, N2 adsorption and desorption isotherms, Fourier transform infrared spectroscopy (FT-IR), and X-ray photoelectron spectroscopy (XPS). The adsorbent showed a much higher adsorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…The Freundlich parameter 1/ n is the degree of adsorption intensity related to the surface heterogeneity. A value of n > 1 indicates a favorable physisorption process; if n = 1, it is a homogeneous adsorption without interaction among the adsorbates; and if n < 1, it is an unfavorable chemisorption process. , Therefore, the values of n ( n > 1) demonstrated that physical force rather than chemical interaction contributed more to polyols adsorption. With increasing temperature, the values of n gradually decreased and n (EG, 1,2-PG) > n (1,3-PG), indicating that polyol adsorption became more unfavorable with increasing temperature and that molecular sieve 10X preferred adsorption of EG (1,2-PG) rather than 1,3-PG.…”
Section: Resultsmentioning
confidence: 99%
“…The Freundlich parameter 1/ n is the degree of adsorption intensity related to the surface heterogeneity. A value of n > 1 indicates a favorable physisorption process; if n = 1, it is a homogeneous adsorption without interaction among the adsorbates; and if n < 1, it is an unfavorable chemisorption process. , Therefore, the values of n ( n > 1) demonstrated that physical force rather than chemical interaction contributed more to polyols adsorption. With increasing temperature, the values of n gradually decreased and n (EG, 1,2-PG) > n (1,3-PG), indicating that polyol adsorption became more unfavorable with increasing temperature and that molecular sieve 10X preferred adsorption of EG (1,2-PG) rather than 1,3-PG.…”
Section: Resultsmentioning
confidence: 99%